COMPARISON AND ANALYSIS OF SPATIAL ELEMENTARY SCHOOL DISTRIBUTION AND TEACHER CERTIFICATION BY DIGITAL MAPPING BASED ON GEOGRAPHIC INFORMATION SYSTEM - Bramasta, Dhi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing her potential, as well as to humanize humans. Uneven distribution or school distribution geographically affect the quality of education of the population in a region. In addition to the comparison of the number of certified and not certified teachers in a school also had a role in influencing the quality of learning in schools. Because the teacher certification is a process competency test for prospective teachers or teachers who want to gain recognition and increase the appropriate competence or chosen profession. Teacher certification is the government's efforts in improving the quality of teachers which is followed by an increase in teachers' welfare. Teachers who have earned certification as an educator declared competent and professional. Data maps are very important information with the information contained within. Data spatial information of GIS-based mapping has a very strategic role in maintaining the integrity of a country, planning and supervision of construction, and arrangement of space. By using geographical based information systems digital mapping, it can be noticed the distribution and spatial patterns of Elementary School distribution as well as the comparison of Elementary School teacher certification in a region.